Pengawasan Ormas Asing dalam Menjaga Ketahanan Nasional di Nusa Tenggara Barat - Tini Apriani; Catur Wibowo (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2018)
The existence of foreign organizations is a consequence of international relations, resulting in interaction between mass organizations in other countries and countries. In line with this, the existence of foreign organizations is regulated by Government Regulation No. 58 of 2016 and Government Regulation No. 59 of 2016. However, there are still people who are concerned about the existence of foreign organizations, which are considered to threaten the values of national unity. Therefore, this study will look at the description of the existence of foreign organizations, namely the flow of foreign organizations into NTB Province, whether their existence is known by the local government; implementation of the role of the community and local government in supervising foreign organizations; and the importance of supervising foreign organizations in order to maintain national security. The method used is descriptive narrative with a qualitative approach. Data collection techniques used library/documentation techniques and interviews with representatives from Bakesbangpoldagri, the Health Office and the Social Service of West Nusa Tenggara Province. The results of the study indicate that Bakesbangpoldagri of West Nusa Tenggara Province does not have accurate data on the existence of foreign organizations; the implementation of the role of the community and local government in supervising foreign organizations has not been realized maximally; and that the supervision of foreign organizations in order to maintain national security is important to be carried out, because the existence of foreign organizations can strengthen and weaken regional resilience, which will affect national security.